The Analysis of Student Errors in Solving Algebraic Math Test Based on TIMSS - Andi Dian Angriani; Fitriani Nur; Dandi Ardiansyah (Indonesian Journal of Mathematics Education, 2023)
The low percentage obtained by students in solving TIMSS problems, especially in the algebra material domain, shows that there are several mistakes that students often make in solving TIMSS-type problems. This study aims to examine students' errors in completing algebraic mathematics tests using the TIMSS (Trends in International Mathematics and Science Study). This was a qualitative descriptive research project in which students of a state junior high school in Sinjai, Sulawesi Selatan, Indonesia, in class VIIIA were the subjects. The research's study instruments included diagnostic tests and interview protocols, and data analysis procedures were separated into three parts: data reduction, data presentation, and conclusion, which involves drawing or verifying. The researchers discovered four kinds of students’ errors in completing algebra tests based on TIMSS that were connected to Newman's category: understanding question errors, transformation errors, process skill errors, and answer writing errors. Furthermore, the cause of errors in answering algebra questions based on TIMSS was that students do not pay more attention when writing information based on the following questions; they do not master the material related to the questions; they have a limited understanding of the material related to the questions; they also forget the concept of multiplication; they do not follow the procedures appropriately; and they do not re-check the answers. As a result, teachers must create TIMSS-based questions to help students improve their mathematical abilities.